CT findings for intracerebral hemorrhage have little incremental impact on post-stroke mortality prediction model performance - Zahuranec, Darin B. (2012)
BACKGROUND: Stroke outcome studies often combine cases of intracerebral hemorrhage (ICH) and ischemic stroke (IS). These studies of mixed stroke typically ignore computed tomography (CT) findings for ICH cases, though the impact of omitting these traditional predictors of ICH mortality is unknown. We investigated the incremental impact of ICH CT findings on mortality prediction model performance. METHODS: Cases of ICH and IS (2000–2003) were identified from the Brain Attack Surveillance in Corpus Christi (BASIC) project. Base models predicting 30-day mortality included demographics, stroke type, and clinical findings (National Institutes of Health Stroke Scale (NIHSS) +/− Glasgow coma scale (GCS)). The impact of adding CT data (volume, intraventricular hemorrhage, infratentorial location) was assessed with the area under the curve (AUC), unweighted sum of squared residuals (Ŝ), and integrated discrimination improvement (IDI). The model assessment was performed first for the mixed case of IS and ICH, and then repeated for ICH cases alone to determine whether any lack of improvement in model performance with CT data for mixed stroke type was due to IS cases naturally forming a larger proportion of the total sample than ICH. RESULTS: A total of 1,256 cases were included (86% IS, 14% ICH). Thirty-day mortality was 16% overall (11% for IS; 43% for ICH). When both clinical scales (NIHSS and GCS) were included, none of the model performance measures showed improvement with the addition of CT findings whether considering IS and ICH together (ΔAUC: 0.002, 95% CI −0.01, 0.02; ΔŜ: −3.0, 95% CI −9.1, 2.6; IDI: 0.017, 95% CI −0.004, 0.05) or considering ICH cases alone (ΔAUC: 0.02, 95% CI −0.02, 0.08; Δ Ŝ: −2.0, 95% CI −9.7, 3.4); IDI 0.065, 95% CI −0.03, 0.21). If NIHSS was the only clinical scale included, there was still no improvement in AUC or Ŝ when CT findings were added for the sample with IS/ICH combined (ΔAUC: 0.005, 95%CI −0.01, 0.02; ΔŜ: −5.0, 95%CI −11.6, 1.0) or for ICH cases alone (ΔAUC: 0.05, 95% CI −0.002, 0.11; ΔŜ: −4.2, 95%CI −11.5, 2.3). However, IDI was improved when NIHSS was the only clinical scale for IS/ICH combined (IDI: 0.029, 95%CI 0.002, 0.065) and ICH alone (IDI: 0.12, 95%CI 0.005, 0.26). CONCLUSIONS: Excluding ICH CT findings had only minimal impact on mortality prediction model performance whether examining ICH and IS together or ICH alone. These findings have important implications for the design of clinical studies involving ICH patients.